Implementation of an Islamic Personal Development Program in Fostering Students Religious Character at SMA IT Rabbani Muara Enim - Mita Haryati; Mardiah Astuti; Muhammad Fauzi (Journal of Educational Sciences, 2026)
This research is motivated by the importance of developing students’ religious character amid increasingly complex social challenges. Religious character development requires not only classroom learning but also continuous habituation and spiritual guidance. This study aims to analyze the implementation of the Islamic Personal Development Program in fostering students’ religious character at SMA IT Rabbani Muara Enim and to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative descriptive approach involving one principal, two Islamic Personal Development (BPI) mentor teachers, one Islamic Religious Education (PAI) teacher, and two twelfth-grade students. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman model. The findings revealed that the program was implemented through mentoring sessions, Tahsin Tahfizh Qur’an (TTQ), congregational prayers, MABIT, dhikr, and rihlah activities. These activities contributed to the development of students’ worship discipline, religious awareness, honesty, and responsibility. Supporting factors included school commitment, mentor teachers, and a religious school environment, while inhibiting factors included low student motivation and limited family support. The study concludes that the Islamic Personal Development Program contributed to the development of students’ religious character through habituation, role modeling, and spiritual experiences.